P016 Colonoids derived from UC patients retain higher transcriptional response to inflammatory triggers in-vitro, even after several passages. (21st January 2022) - Abbas Egbariya, H; Ben-Shoshan, M; Braun, Z; Berger, T; Granot, M; Loberman-Nachum, N; Vais, B; Gal Mor, O; Amir, A; Haberman, Y
Abstract: Background: Ulcerative colitis (UC) patients show high variations in disease phenotype and response to therapy. Intestinal epithelia play a key role in UC pathogenesis, and therefore patient-derived epithelial model to study this variation are warranted. Few studies suggest that colonoids derived from UC patients retain some disease-related transcriptional and epigenetic changes, but they also raise questions regarding their persistence in culture. Here, we aimed to characterize if UC epithelial dysfunctions and response to inflammatory signals retained in colonoid culture. Methods: Rectal biopsies were used to generate epithelial organoids (colonoids) that were grown through 5–10 passages using L-WRN conditioned medium. Media and total RNA were collected for measuring CXCL1 secretion using ELISA and qPCR, respectively. Results: 3 control and 5 UC patients-derived colonoids were generated. Median age was 17 years and 75% were females. Control patients were evaluated for loose stool, abdominal pain, and anemia, but had normal rectal mucosa endoscopically and histologically. UC included newly diagnosed and established patients. Colonoids were allowed to differentiate for 48 hours before applying different inflammatory cocktails to induce inflammation for 24 h with IFNγ+LPS, IFNγ+TNFα, and TNFα+LPS (20 ng/ml each trigger). UC organoids secreted significant higher levels of CXCL1 as detected in the media at baseline (p=0.02) and with IFNy+TNFa (p=0.01), but no difference was noted with TNFa+LPS (Fig. 1 ). In addition, CXCL1 mRNA showed significant higher levels after inflammatory triggering in UC vs. controls (Fig. 1 ) with IFNγ +LPS, (p=0.02), IFNγ+TNFα (p=0.003), and TNFα+LPS (p=0.016). Similarly, several other genes showed significant and substantial induction in UC organoids vs. controls, in some or all the inflammatory triggers (Fig. 2 ). The tight junction-associated protein, ZO1 showed substantially higher induction in UC compared to controls with the 3 inflammatory cocktails [IFNγ +LPS, (p=0.03), IFNγ+TNFα (p=0.02), and TNFα+LPS (p=0.005)]. Significantly higher expression in UC organoid was further noted in comparison to control in IL8 levels upon IFNγ +LPS (p=0.002), in interferon inducible IDO1 with IFNγ+TNFα (p=0.001), and in goblet associated MUC2 (p=0.04) and bacterial sensing DUOX2 (p=0.001) with TNFα+LPS. Conclusion: Our data suggest that UC colonoids retain some inflammatory response activity in-vitro even after several passages. We show that UC organoids secrete higher level of CXCL1. Additionally, we note higher transcriptional response to different inflammatory signals in UC organoids potentially implying an "immune" epithelial transcriptional memory that may contribute to UC chronicity.